2003
DOI: 10.1038/sj.leu.2403076
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor and its receptors in multiple myeloma

Abstract: Multiple myeloma (MM) progresses from an avascular to a vascular phase (active MM) accompanied by a significant increase in microvessel density in the bone marrow. This article summarizes the literature concerning the specific role played by vascular endothelial growth factor (VEGF) in this process. Recent applications of antiangiogenic agents that interfere with VEGF signaling and block MM progression are also described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 76 publications
1
42
0
Order By: Relevance
“…The key mechanism involved in such effect was the inhibition of angiogenesis, which caused ischemic necrosis in the tumors. IL-27 induced the downregulation of different proangiogenic molecules, including some MM growth factors, such as IL-6, VEGF-D, and CCL2 (40,41). Although VEGF-D and CCL2 were downregulated in tumors formed in IL-27-treated mice and in IL-27 in vitro treated primary MM cells, IL-6 was not detected in primary MM cells.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The key mechanism involved in such effect was the inhibition of angiogenesis, which caused ischemic necrosis in the tumors. IL-27 induced the downregulation of different proangiogenic molecules, including some MM growth factors, such as IL-6, VEGF-D, and CCL2 (40,41). Although VEGF-D and CCL2 were downregulated in tumors formed in IL-27-treated mice and in IL-27 in vitro treated primary MM cells, IL-6 was not detected in primary MM cells.…”
Section: Discussionmentioning
confidence: 90%
“…Here, we showed that human primary MM cells expressed functional IL-27R, and IL-27 triggering affected their angiogenic activity, whereas it did not attract tumor cells in chemotaxis assays nor affected their apoptosis, proliferation, or cytokine release. IL-27 influenced the expression of a wide panel of angiogenesisrelated genes and inhibited different proangiogenic factors such as VEGF-D and CCL2, two of the major MM growth factors (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that myeloma cells directly produce VEGF [37][38][39]. Moreover, VEGF produced by myeloma cells stimulates interleukin-6 (IL-6) and VEGF secretion by BM stromal cells that in turn induce VEGF production by myeloma cells in a paracrine fashion [40,41].…”
Section: Vascular Endothelial Growth Factor (Vegf)mentioning
confidence: 99%
“…Several studies show overexpression and secretion of vascular endothelial growth factor (VEGF) by the clonal plasma cells (Ria et al, 2003). Vascular endothelial growth factor stimulates proliferation and chemotaxis in both endothelial cells (EC) via VEGF receptor-2 (VEGFR-2) and stromal cells via VEGFR-1.…”
Section: Angiogenesis In Multiple Myelomamentioning
confidence: 99%